Assessment of readiness of a traffic environment for autonomous delivery robots - Arntz, E. M.; Van Duin, J. H. R.; Van Binsbergen, A. J.; Tavasszy, L. A.; Klein, T. (Frontiers in Future Transportation, 2023)
Introduction: Autonomous delivery robots are a promising alternative for last-mile delivery. To realise successful implementation of delivery robots in public spaces, it is important to study the interaction between robots and the traffic environment. The traffic environment includes the physical infrastructure and the objects using it like cars and people. Methods: This research proposes an assessment method to determine the readiness of a traffic environment for autonomous delivery robots. A conceptual model is proposed that includes the factors that determine this so-called “roboreadiness”. The two key components of the model are the performance of the robot in the traffic environment and its social acceptance. A real-life experimental test case, expert interviews, and a survey are used to refine and validate the framework. Results: The real-life test case showed for the basic variant a sufficient level both on performance and social acceptance. All other variants such as pillars, road narrowing, and bends did not lead to sufficient performance or social acceptance levels. Discussion: The main outcome of this research is an assessment framework which allows to quantitatively assess traffic performance and social acceptance of sidewalk automated delivery robots. Suggestions for future work include further detailing and elaboration of the approach, scaling up experiments, and researching the possible influence of social acceptance on traffic performance.